Teaching English for Young Learners (TEYL): A Literature Study - Pratama, Albert Diaz (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
Teaching English for Young Learners (TEYL) has gained significant attention in recent years due to the increasing importance of English as a global language. This literature study explores the current trends, challenges, and effective strategies in TEYL by analyzing recent scholarly works published between 2020 and 2024. The study highlights the importance of age-appropriate methodologies, technology's role, and cultural context's impact on teaching English to young learners. By synthesizing findings from various studies, this article provides insights into best practices and future directions for TEYL research and pedagogy.